EGFR confers radioresistance in human oropharyngeal carcinoma by activating endoplasmic reticulum stress signaling PERK‐eIF2α‐GRP94 and IRE1α‐XBP1‐GRP78. (9th November 2018) - Zhang, Miao; Han, Ning; Jiang, Yuanjun; Wang, Jie; Li, Gaiyan; Lv, Xintong; Li, Guang; Qiao, Qiao
Abstract: The activation of epidermal growth factor receptor (EGFR) is associated with radioresistance in malignant tumors. Specifically, radiation can destroy endoplasmic reticulum (ER) homeostasis to induce ER stress (ERS). However, the effect of EGFR‐mediated regulation of ERS signaling pathway on radiosensitivity has not yet been reported. The present study showed that silencing EGFR increased radiosensitivity of both radiosensitive and radioresistant oropharyngeal squamous cell carcinoma (OSCC) cells by inhibiting ER stress signaling (PERK‐eIF2α‐GRP94 and IRE1α‐XBP1‐GRP78). This effect was abolished by pretreatment with EGF, however. In addition, knockdown of EGFR in OSCC cells inhibited DNA double‐stand break repair and autophagy while increased radiation‐induced apoptosis. Conversely, activating ERS inhibited the aforementioned functions. Furthermore, EGF increased ER stress‐independent ERK and AKT signaling upon irradiation of OSCC cells. Immunohistochemical analysis of 80 tissue samples from OSCC patients showed that co‐expression of EGFR and PERK was associated with poor prognosis. It thus appears EGFR confers radioresistance in OSCC by activating ER stress signaling. These results suggested that the cooperative effects of radiotherapy and EGFR‐targeted inhibitor therapy can be further improved by inhibiting PERK‐eIF2α‐GRP94 and IRE1α‐GRP78 in non‐response oropharyngeal carcinoma patients. Abstract : EGFR conferred radioresistance in OSCC cells by activating ERS signalling PERK‐eIF2α‐GRP94 and IRE1α‐XBP1‐GRP78. Knockdown of EGFR in OSCC cells inhibited DNA double‐strand break repair and autophagy mediated by ERS. Co‐expression of EGFR and PERK was associated with poor prognosis of OSCC.